Population pharmacokinetics and exposure‐response analyses of teduglutide in adult and pediatric patients with short bowel syndrome - Jean‐Francois Marier (Wiley, 2021)
Abstract Teduglutide is a recombinant analog of human glucagon‐like peptide‐2 that regulates the functional and structural integrity of the cells lining the gastrointestinal tract. Teduglutide is approved for the treatment of patients with short bowel syndrome (SBS) who are dependent on parenteral support (PS). Population pharmacokinetic (PK) and exposure‐response analyses were performed to support teduglutide dosing in patients with SBS. The analysis included 219 patients with SBS (aged <1 year, 5 patients; 1–11 years, 86 patients; 12–17 years, 8 patients; 18–79 years, 120 patients), and 259 non‐SBS subjects (including healthy volunteers and subjects with renal or liver impairment). A one‐compartment model with first‐order absorption and linear elimination adequately characterized the PKs of teduglutide. In patients with SBS, the apparent clearance (CL/F), volume of distribution (V/F), and elimination half‐life of teduglutide were 16.0 L/h, 33.9 L, and 1.47 h, respectively. CL/F depended on body weight and renal function, and V/F depended on body weight and age. Maximum concentration (Cmax) of teduglutide was similar in adult and pediatric patients, and in Japanese and non‐Japanese patients. A time‐ and exposure‐response model dependent on the Cmax of teduglutide adequately characterized the reduction in PS over more than 2 years of treatment. Daily dosing of 0.05 mg/kg teduglutide resulted in a maximum reduction in PS of 5.76 L/week. Higher Cmax values were associated with a more important reduction in PS over time. Adult and pediatric patients with SBS presented similar PKs and response to teduglutide.